2018
DOI: 10.1007/s00425-018-2923-9
|View full text |Cite
|
Sign up to set email alerts
|

The histone acetyltransferase GCN5 and the transcriptional coactivator ADA2b affect leaf development and trichome morphogenesis in Arabidopsis

Abstract: The histone acetyltransferase GCN5 and associated transcriptional coactivator ADA2b are required to couple endoreduplication and trichome branching. Mutation of ADA2b also disrupts the relationship between ploidy and leaf cell size. Dynamic chromatin structure has been established as a general mechanism by which gene function is temporally and spatially regulated, but specific chromatin modifier function is less well understood. To address this question, we have investigated the role of the histone acetyltrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…In addition, noncoding RNAs also play important roles in plant development as epigenetic regulators (Boyko and Kovalchuk, ; Davila‐Velderrain et al ., ; Grant‐Downton and Dickinson, ; Steimer et al ., ; Yamamuro et al ., ). A recent study showed that a multifunctional histone acetyltransferase, AtGCN5, positively influences trichome branching with possible regulation of TRY (Kotak et al ., ). On the other hand, through regulating histone acetylation of the promoters of GL1, GL2, GL3 and CPC, GCN5 is also involved trichome initiation regulation (Wang et al ., ).…”
Section: Epigenetic Modifications Underlying Trichome Development In mentioning
confidence: 97%
“…In addition, noncoding RNAs also play important roles in plant development as epigenetic regulators (Boyko and Kovalchuk, ; Davila‐Velderrain et al ., ; Grant‐Downton and Dickinson, ; Steimer et al ., ; Yamamuro et al ., ). A recent study showed that a multifunctional histone acetyltransferase, AtGCN5, positively influences trichome branching with possible regulation of TRY (Kotak et al ., ). On the other hand, through regulating histone acetylation of the promoters of GL1, GL2, GL3 and CPC, GCN5 is also involved trichome initiation regulation (Wang et al ., ).…”
Section: Epigenetic Modifications Underlying Trichome Development In mentioning
confidence: 97%
“…To identify the members of HB genes in moso bamboo, the previously identified HB genes of Arabidopsis thaliana and Oryza sativa were retrieved from the database TAIR 10.0 (The Arabidopsis Information Resource, https://www.arabidopsis.org/) and RGAP 7.0 (Rice Genome Annotation Project, http://rice.plantbiology.msu.edu/), respectively [37,38], and were used as queries in BLAST searches against the database of the moso bamboo genome (BambooGDB, http://bamboo.bamboogdb.org/) [28]. The sequences were selected for further analysis if the E-value was less than 1 × 10 −10 .…”
Section: Identification Of Hb Genes In Moso Bamboomentioning
confidence: 99%
“…GCN5 and ADA2b affect the developmental transition from the juvenile to adult phase by controlling the expression of SQUAMOSA PROMOTER BINDING PROTEIN-LIKE (SPL) factors [65]. GCN5 and ADA2b also affect several aspects of leaf cell growth and division, including in endoreduplication and trichome morphology [66,67].…”
Section: The Biological Role Of Gcn5 and Ada2b In Plantsmentioning
confidence: 99%